2014
DOI: 10.2478/aoter-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady natural convection in micropolar nanofluids

Abstract: This paper presents the analysis of momentum, angular momentum and heat transfer during unsteady natural convection in micropolar nanofluids. Selected nanofluids treated as single phase fluids contain small particles with diameter size 10-38.4 nm. In particular three water-based nanofluids were analyzed. Volume fraction of these solutions was 6%. The first of the analyzed nanofluids contained TiO2 nanoparticles, the second one contained Al2O3 nanoparticles, and the third one the Cu nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…From Figures. 8-9, It is identified that an escalating of Γ and Ω causes a decrease and an increase in velocity and angular velocity respectively, which is analogous with the recorded consequences of Rup and Nering [16], Nering and Rup [17]. Micropolar Parameter, Γ, has much influence on the velocity field than Micro-inertia parameter, Ω.…”
Section: Upshots and Argumentmentioning
confidence: 68%
See 2 more Smart Citations
“…From Figures. 8-9, It is identified that an escalating of Γ and Ω causes a decrease and an increase in velocity and angular velocity respectively, which is analogous with the recorded consequences of Rup and Nering [16], Nering and Rup [17]. Micropolar Parameter, Γ, has much influence on the velocity field than Micro-inertia parameter, Ω.…”
Section: Upshots and Argumentmentioning
confidence: 68%
“…Rahman et al [15] measured how much-differentiated heat generation and electric conductivity affect micropolar fluid and also elaborated their outcomes, taking the variable fluid viscosity along with variable thermal conductivity into account. Another worth noting approach was addressed by Rup and Nering [16] to scrutinising three water-based nanofluids (TiO2, Al2O3, and Cu), occupying the diameter approximately 10-38.4 nm, considering as single-phase fluids. On the other hand, an extended approach was also made by Nering and Rup [17], where water-based and ethylene-glycol mixed nanofluids were crucially utilised to determine the volume fraction solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postrzednik [20] has studied the influence of the heat transfer on the specific thermal capacity of the flowing compressible fluid. The unsteady natural convection in micropolar nanofluids has been studied by Rup and Nering [21].…”
Section: Introductionmentioning
confidence: 99%
“…Magneto-micropolar fluid with nano particles plays a vital rule in the view of its wide applications in many engineering problems such as electric transformers, heating elements and nano technology. Kazimierz et al [1] and [4] analyzed the unsteady natural convection in micropolar nano fluids, where the increasing heat exchange due to natural convection in water solutions of Al2O3, TiO2 and Cu with properties of micropolar nano-fluids in the vicinity of vertical plate heated by heat flux of q0 that rises suddenly. A vast investigation of convective heat transfer in nano-fluids by Buongiorno [2] predicted that the nano-particles' absolute velocity is roughly a sum of the base fluid velocity and the slip velocity.…”
Section: Introductionmentioning
confidence: 99%